The potential value of priority-setting methods in public health investment decisions: qualitative findings from three English local authorities. Issue 5 (19th October 2016) - Hunter, D. J.; Marks, L.; Brown, J.; Scalabrini, S.; Salway, S.; Vale, L.; Gray, J.; Payne, N.
Abstract: This paper reports on an action-oriented research study providing decision support to three local authorities in England on the prioritisation of public health investment and disinvestment decisions. We adopted a political science perspective, using the multiple streams framework to investigate the use of prioritisation tools in public health spending decisions at a time of severe financial constraints. The challenges and implications of their potential use in everyday practice were explored. Twenty-nine interviews were conducted before the targeted decision support occurred and 19 interviews after the decision support had been delivered. Interviews were held with locally elected politicians, officers and public health professionals based within local government, NHS commissioners and the local independent consumer watchdog for health and social care. Targeted workshops with local stakeholders were facilitated in each site by health economist members of the project team. Structured observational notes were recorded during these workshops and integrated with the interview data. Many respondents expressed an interest in prioritisation tools although some scepticism was expressed about their value and impact on decision-making. This paper analyses the enablers and barriers to adopting priority-setting tools in a local government environment that by definition is political. The findings suggest that the adoption of priority-setting tools in decision-making processes in public health poses some significant challenges within local government and that certain enabling factors have to be present.